Seasonal development of Micraspis discolor Fabricius in condition of northern vietnam - Con, Vu Quang; Mai, Pham Quynh (Academia Journal of Biology, 2012)
Adult of Micraspis discolor can be observed on field during from March to October the year easily. In the field, the development stages of M. discolor such as egg, larva, and pupa often appear during this time. It is very difficult to observe them during the cold weather months of the winter from November to February. The adults are wintering under grass or dry leaves on soil usually. At this crisis period time, eggs are not being formed in the ovarium which shriveled up this phenomenon manifest itself the shallow diapauses of the species. In the seasonal development the M. discolor can be developing many generations in a year and have generation overlap phenomenon. In Hanoi area, M. discolor lays eggs and develop during about 8- 9 months in a year. There are 3 peaks of the oogenesis in year. The first time appear in March second – May and the third - September, October.